The Effectiveness of the Non-Cash Food Assistance Program (BPNT) during the Covid-19 Period in Bireuen Regency - Ti Aisyah; Cut Sukmawati; Muhammad Hasyem; Nur Aklima (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2021)
Non-Cash Food Assistance (BPNT) aims to reduce the burden of public spending in meeting basic needs. However, there are some problems with distribution. This research focuses on indicators of the effectiveness of the distribution of the BPNT assistance program, namely target accuracy, choice accuracy, and timeliness, as well as the benefits of the BPNT program for the community. This study uses a qualitative approach with a descriptive method. The types of data used are primary and secondary data. Data collection techniques through observation, interviews and documentation. The results of the study illustrate that the effectiveness of the distribution of non-cash food assistance in Bireuen Regency has not been fully running well because BPNT recipients are not on target. Meanwhile, KPM is not given the freedom to choose aid materials according to their needs, so it is not the right choice. In addition, the schedule for assisting is still not following the provisions so that it is not on time. The benefits of the program can be directly felt by the poor in improving food security and improving the economy for SMEs (e-Warung). Overall, the distribution of Non-Cash Food Assistance (BPNT) to KPM is still less effective. ABSTRAKBantuan Pangan Non Tunai (BPNT) bertujuan mengurangi beban pengeluaran masyarakat dalam pemenuhan kebutuhan pokok. Namun dalam penyaluran terdapat beberapa permasalahan.  Penelitan ini berfokus pada indikator efektivitas penyaluran program bantuan BPNT yaitu ketepatan sasaran, ketepatan pilihan, dan ketepatan waktu, serta manfaat program BPNT bagi masyarakat. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Jenis data yang digunakan adalah data primer dan sekunder. Teknik pengumpulan data melalui observasi, wawancara dan dokumentasi. Hasil penelitian menggambarkan bahwa efektivitas penyaluran bantuan pangan non tunai di Kabupaten Bireuen belum sepenuhnya berjalan dengan baik karena penerima BPNT tidak tepat sasaran. Sementara KPM tidak diberikan kebebasan dalam pemilihan bahan bantuan sesuai dengan kebutuhan sehingga tidak tepat pilihan. Selain itu, jadwal pemberian bantuan masih belum sesuai dengan ketentuan sehingga tidak tepat waktu. Adapun manfaat program langsung dapat dirasakan oleh masyarakat kurang mampu dalam meningkatkan ketahanan pangan dan meningkatkan ekonomi bagi pelaku UKM (e-Warung).  Secara keseluruhan penyaluran Bantuan Pangan Non Tunai (BPNT) kepada KPM masih kurang efektif.